Girolamo Borsieri. Un colto poligrafo del Seicento Con un inedito "Il Salterio Affetti Spirituali" - Piazzesi, Sandro (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2009)
Girolamo Borsieri (Como 1588-1629), a versatile intellectual of ranging interests, was greatly appreciated by his contemporaries for the breadth of his literary, artistic and historical knowledge and for his witty and laconic style. Among his admirers were Federico Borromeo and Giovan Battista Marino. In the twentieth century his intellectual standing was acknowledged in works of art history criticism, which were followed by other contributions of literary, linguistic and musicological interest. Despite this, even now many of his works appear to have been somewhat neglected. Starting from the writer's own reflections and the suggestions offered by the critics, the present work proposes a key to the reading of Borsieri as a man, an intellectual and a theorist. It is a monograph on Girolamo Borsieri, constructed largely upon first-hand manuscript and autograph materials that make it possible to sketch his biographical profile and the why and how of his participation in the cultural and religious renewal of Lombard society in the early decades of the seventeenth century. Borsieri's writings are presented, and their critical reception traced. His sacred madrigals - Il Salterio Affetti Spirituali - are also published here for the first time, from the autograph.